The push-out bond strength of three root canal materials used in primary teeth: in vitro study - Özer, Hazal; Abaklı İnci, Merve and Açar Tuzluca, Sevcihan (Frontiers in Dental Medicine, 2023)
The study aims to compare the bond strength of three primary tooth root canal filling materials to the root canal wall with a push-out test (Calplus, DiaPaste, BIOfactor MTA). First, 30 primary central teeth were cut transversely using a water-cooled low-speed diamond saw vertical to the long axis to obtain 2 mm thick discs from the middle third of the roots. Next the materials used were placed on dentin discs and kept in an incubator for 1 week at 37°C and 100% humidity until the hardening mechanism of the root-canal sealer was completed. Finally, a vertical force was placed on each material from apical to coronal with a 0.75 mm diameter stainless steel cylindrical piston without contacting the root canal dentin. The data were analyzed using the SPSS 22.0 program and the Mann-Whitney U test was used as a post hoc test. There was a statistically significant difference between the bonding values of different primary tooth root canal sealers to root canal dentin (p < 0.05). Among the maximum binding values, the lowest measurement was in Calplus (0.43 ± 0.28 MPa), and the highest measurement was in BIOfactor MTA (24.24 ± 17.78 MPa) (p < 0.05). BIOfactor MTA has a higher bonding value to root canal dentin than calcium hydroxide-based primary tooth canal sealers.